The impact of COVID-19 pandemic on medical education: Iran's experience at the outset of the pandemic - Maniati, Mahmood (International Journal of Education and Cognitive Sciences, 2022)
The purpose of this study was to investigate the impact of COVID-19 pandemic on medical education at the outset of the pandemic. It was a descriptive web-based research, we asked the students of medical universities across the country about the educational status of Iranian medical universities during this epidemic. After reaching the desired sample size (585 people), the received data were analyzed using SPSS statistical software version 22. The data were collected in March 2020. In all universities, an online system provided by the Ministry of Health and Medical Education (called NAVID) Data from 585 students in the study showed The majority (28.3%) of students were from the school of allied medical sciences, followed by nursing and midwifery (24.2%) and the lowest participation (6.6%) was from the school of medicine. The majority (more than 80%) of the students still had no idea when classes and internship courses would start and when they would return to university. we learn is related to students of medical sciences , they need to be educated both in theory and practice on how to provide services under epidemic conditions, and this should be included in their curriculum.